THE STATE OF THE QUESTION OF ASSESSING OF CAR EFFICIENCY IN URBAN ENVIRONMENTS (British Journal of Global Ecology and Sustainable Development, 2024)
Design development and growth in the number of vehicles and the increase in varieties of fuel requires a modern approach to estimating fuel-economic characteristics of cars. The article discusses the foundations and objectives method of evaluation of car efficiency in urban environments. In the paper given the results of experimental studies to determine the condition of the driving modes of Tashkent city and justification of the relevance and objectives of the study evaluating of cars efficiency in urban environments.